Exploration of the Tumor Immune Landscape and Identification of Two Novel Immunotherapy-Related Genes for Epstein-Barr virus-associated Gastric Carcinoma via Integrated Bioinformatics Analysis - Deng, Shi-Zhou; Wang, Xiang-Xu; Zhao, Xing-Yu; Bai, Yin-Miao; Zhang, Hong-Mei (Frontiers in Surgery, 2022)
Epstein–Barr virus (EBV)-associated gastric carcinoma (EBVaGC) is a specific molecular subtype of gastric carcinoma with a high proportion of tumor-infiltrating lymphocytes (TIL). It is a highly immunogenic tumor that may benefit from immunotherapy. Hence, it is imperative to analyze the immune landscape and identify immunotherapy biomarkers for EBVaGC. In our study, we investigated the immune landscape and identified 10 hub genes for EBVaGC via integrated bioinformatics analysis. We found that EBVaGC expressed more immune-related genes, including common immune checkpoints (ICPs) and HLA genes, than EBVnGC. The immune score in EBVaGC was higher, which means EBVaGC has greater immune cell infiltration. Ten hub genes (CD4, STAT1, FCGR3A, IL10, C1QA, CXCL9, CXCL10, CXCR6, PD-L1, CCL18) were detected, which are candidate biomarkers for EBVaGC. Two hub genes, CXCL9 and CXCR6, were identified as novel immunotherapy-related genes. Taken together, the results of our comprehensive analysis of the immune microenvironment of EBVaGC revealed its unique immune landscape, demonstrating that it is a highly immunogenic tumor. Moreover, we identified hub genes that may serve as potential immunotherapy biomarkers for EBVaGC.